Radio Rajdowe Rozgłośni Regionalnej Polskiego Radia w Olsztynie 1998–2016 - Szydłowska, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Radio, seen as an accompanying medium needs to participate in the evolution of needs: change its style, create new forms of mutual relations, make use of a multitude of genres resulting from its multimedia status. In a certain sense radio is becoming a new medium, although it happily avails itself of its previously acquired attributes. In this context, the subject we are addressing is clearly included in this definitional composition. “Radio Rajdowe” is a specific media construction, the only initiative of its kind in public radio in Europe. It is a form created by the presence of the broadcaster in the public space. A broadcaster that is its chronicler and participant. It is also an event and an interesting project, well adapted to the Internet. It is the quintessence of the broadcaster-listener correlation, a symbiotic radio structure, combining in one the parent station and its creative “progeny”. It is an interesting communicative phenomenon, and thus worthy of such attention and analysis.